The cocrystal structure of praziquantel-hesperetin (1/1), C35H38N2O8 - Han Wei; Li Mei; Geng Xiang; Zhang Guoshun (Zeitschrift für Kristallographie - New Crystal Structures)
C35H38N2O8, monoclinic, P21 (no. 4), a = 14.0502(3) Å, b = 5.93007(14) Å, c = 18.3417(4) Å, β = 101.327(2)°, V = 1498.45(6) Å3, Z = 2, Rgt (F) = 0.0443, wRref (F 2) = 0.1082, T = 100(2) K.